Ø§Ù„Ø§Ø®ØªØ¨Ø§Ø± Ù„Ù…Ù‡Ø§Ø±Ø© Ø§Ù„Ù‚Ø±Ø§Ø¡Ø© ÙÙŠ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© - Nuruddin, Alfy Mamduh; Vetiana, Gautama Veri (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2021)
An essential tool in the educational is process, and we couldn’t do without it. Carry out this evaluation in order to get input or update in the process and educational goals. Student learning outcomes are not limited to cognitives aspect, but also three aspect such cognitive, emotional ad psychological. Amd then teach the teacher to evaluate these three aspect. In the evaluation process. Teachers are ecpected to understand the reality of learning and its results and classify the result, even evaluation tools. One such tool is a test. This test is held to evaluate the student an defind out the extent of his mastery, the extent of his progress and where he is in relation to his peers, This test has different types, its use varies according to needs and situation. Among these tests is the reading test, this test requires student proficiency in reading comprehension to answer the following questions. Therefore, have to teacher understands the steps in developing the test properly to achieve the desired goals in the evaluation process. Evaluasi merupakan alat penting dalam proses pendidikan, pelaksaan evaluasi dilakukan agar mencapai masukan dan pembaharuan dalam proses dan tujuan pendidikan. Hasil belajar siswa tidak terbatas pada aspek kognitif saja, tetapi juga pada tiga aspek yaitu kognitif, emosional dan psikologis, perlu diketahui agar guru mengevaluasi ketiga aspek tersebut. Dalam proses evaluasi, guru diharapkan memahami realitas pembalajaran dan hasilnya serta mengklarivikasi hasil-hasilnya, bahkan alat evaluasi, salah satu alatnya adalah tes. Tes ini diadakan guna mengevaluasi siswa dan mengetahui sejauh mana penguasaannya, sejauh mana kemajuannya. Tes ini memiliki jenis yang berbeda-beda penggunaannya bervariasi sesuai dengan kebutuhan dan situasi. Diantara tes tersebut adalah tes membaca, tes ini menuntut kemahiran siswa dalam pemahaman hingga menjawab pertanyaan-pertanyaan berikutnya. Oleh karena itu, guru memahami langkah-langkah dalam pengembangan tes tersebut dengan baik untuk mencpai tujuan yang diinginkan dalam proses evaluasi.